Poster girl - Roth, Veronica (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"What's right is right. Sonya Kantor knows this slogan--she lived by it for most of her life. For decades, everyone in the Seattle-Portland megalopolis lived under it, as well as constant surveillance in the form of the Insight, an ocular implant that tracked every word and every action, rewarding or punishing by a rigid moral code set forth by the Delegation. Then there was a revolution. The Delegation fell. Its most valuable members were locked in the Aperture, a prison on the outskirts of the city. And everyone else, now free from the Insight's monitoring, went on with their lives. Sonya, former poster girl for the Delegation, has been imprisoned for ten years when an old enemy comes to her with a deal: find a missing girl who was stolen from her parents by the old regime, and earn her freedom. The path Sonya takes to find the child will lead her through an unfamiliar, crooked post-Delegation world where she finds herself digging deeper into the past--and her family's dark secrets--than she ever wanted to" --